Evaluation of the Community Empowerment Program Conducted by PT PLN Indonesia Power UBP Mrica Unit PLTA of Wonogiri - Sugiyo; Ramdani, Tober; Rohmanto, Sodik; Mar Ah, Nurmala Khoirul (Global Writing Academica Researching & Publishing, 2024)
The number of business entities in Wonogiri Regency has been consistently increasing. Wonogiri District has the potential to become a hub for new business development or product diversification, as recent data indicates that there are only about 217 MSMEs (3% of the total in Wonogiri Regency). In response to this situation, PT PLN Indonesia Power UBP Mrica Unit PLTA of Wonogiri has implemented a Corporate Social Responsibility (CSR) program focusing on the empowerment of the Iwak Presto MSME Upscalling in Wuryorejo Village, Wonogiri Regency, Central Java. This program aimed to address the challenges faced by food processing MSMEs in the region and capitalize on the significant potential of the Gajah Mungkur Reservoir fishery. The program assisted in the form of a production set and packaging equipment for the Iwak Presto MSME, which increased productivity by up to 100.69% and elevated the targeted group to a local hero status. Despite showing positive impacts, there remain gaps that require further evaluation and strategic follow-up to support long-term growth.